Curriculum Management in Advanced Islamic Educational Institutions - Nisak, Hernik Khoirun (Jurnal Paradigma, 2022)
The curriculum as a design in education has a strategic position, because all educational activities lead to the curriculum. Once the importance of the curriculum as a center for educational activities, in its preparation it requires a strong foundation and foundation, through in-depth thinking and research. Islamic Religious Education Curriculum is Islamic religious education materials in the form of activities, knowledge and experiences that are intentionally and systematically given to students in order to achieve the goals of Islamic Religious Education. Islamic religious education curriculum is a tool to achieve the goals of Islamic education. The scope of Islamic Religious Education material is the Qur'an, and hadith, faith, morality, Fiqh / worship, and history. The curriculum has a very essential place in the progress of educational institutions, it must be recognized that the success of curriculum implementation is strongly influenced by the ability of the teacher who will implement and actualize the curriculum, the teacher's ability is mainly related to the knowledge and abilities and tasks assigned to him.